Geographical Variations in Patterns of DAPT Cessation and Two-Year PCI Outcomes: Insights from the PARIS Registry - Vogel, Birgit; Chandrasekhar, Jaya; Baber, Usman; Mastoris, Ioannis; Sartori, Samantha; Aquino, Melissa; Krucoff, Mitchell W.; Moliterno, David J.; Henry, Timothy D.; Weisz, Giora; Gibson, C. Michael; Iakovou, Ioannis; Kini, Annapoorna S.; Farhan, Serdar; Sorrentino, Sabato; Faggioni, Michela; Colombo, Antonio; Steg, Philippe Gabriel; Witzenbichler, Bernhard; Chieffo, Alaide; Cohen, David J.; Stuckey, Thomas; Ariti, Cono; Dangas, George D.; Pocock, Stuart; Mehran, Roxana (Thrombosis and Haemostasis, 2019)
Background Data on geographical variations in dual antiplatelet therapy (DAPT) cessation and the impact on outcomes after percutaneous coronary intervention (PCI) are limited. We sought to evaluate geographical patterns of DAPT cessation and associated outcomes in patients undergoing PCI in the United States versus Europe.Methods Analyzing data from the PARIS registry, we studied 3,660 U.S. patients (72.9%) and 1,358 European patients (27.1%) that underwent PCI with stent implantation. DAPT cessation was classified as physician-recommended discontinuation, interruption (< 14 days), or disruption due to bleeding or noncompliance. The primary endpoint was 2-year major adverse cardiovascular events (MACE) defined as a composite of cardiac death, stent thrombosis, myocardial infarction, or target lesion revascularization.Results Cardiovascular risk factors were more common in the United States, whereas procedural complexity was greater in Europe. The incidence of 2-year DAPT discontinuation was significantly lower in U.S. versus European patients (30.7% vs. 65.6%; p < 0.001); however, rates of interruption (13.7% vs. 1.5%, p < 0.001) and disruption (17.7% vs. 5.1%, p < 0.001) were higher. DAPT discontinuation was associated with lower adjusted risk, whereas DAPT disruption was associated with greater risk for 2-year MACE, without interaction by region. After adjustment for baseline characteristics and DAPT cessation, 2-year MACE risk was not statistically different between regions (10.3% for Europe vs. 11.9% for U.S., adjusted hazard ratio 0.81, 95% confidence interval 0.65–1.01, p = 0.065).Conclusion DAPT cessation patterns, along with clinical and angiographic risk, vary substantially between PCI patients in the U.S. versus Europe. Despite such differences, cardiovascular risk associated with DAPT cessation remains uniform.
Keywords: dual antiplatelet therapy; percutaneous coronary intervention; dual antiplatelet therapy cessation; geographical differences; adherence